A study on the surgical treatment of ingrowing toe nail with nail excision with chemical matricectomy versus nail excision alone - Ashutosh Talwar; Neerja Puri (Our Dermatology Online, 2013)
An in growing toenail develops when the proper fit of the nail plate in the lateral nail groove is altered. We selected 30 patients of ingrowing toe nail for the study. The patients were divided into two groups of 15 patients each. In group I patients, nail avulsion with chemical matrictectomy with 88%phenol was done. In group II only nail avulsion was done. In group I patients the surgical success rate was 98% and in group II, the surgical success rate was 86.6%. No patient complained about the cosmetic appearance of toe nail after the operation.